Language, Cognition and Identity. Extensions of the endocentric/exocentric language typology - Korzen, Iørn; Cresti, Emanuela (Strumenti per la didattica e la ricerca, 2010)
An endocentric language is a language whose verbs are lexically precise and concrete whereas its nouns are abstract and vague. An exocentric language has lexically precise and concrete nouns and abstract verbs. The Germanic languages prove to be endocentric and the Romance languages exocentric. The lexical differences entail differences at other levels as well, linguistic as well as extralinguistic. This multilingual volume contains a selection of papers presented at the two day Italian-Danish linguistic seminar Lingua, cognizione e identità: estensioni della tipologia delle lingue endo- ed esocentriche held at the Italian Department of the University of Florence on the 22nd and 23rd of September 2009. The papers challenge the endo-/exocentric approach at various levels (lexicon, grammar, language infrastructures, socio cultural reflections) with examples from the Romance languages (Italian and French) and the Germanic languages (English, German and Danish).